Studi Eksperimen untuk Kondisi Tanpa Beban pada Pengering Ikan Tipe Greenhouse Aktif - Sigit Deddy P. Sidhi; Andreas Pujianto; Muhfizar Muhfizar; Djoko Prasetyo (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2017)
Among all available renewable energy sources, solar energy is the most abundant one and is available in both direct as well as indirect forms. People have applied solar energy as energy alternative in various fields. One of the field that use solar energy is drying. Drying is one of the best methods to preserve product like fish. Fish drying is practice to preserve the fish for longer duration. Entrapment of thermal energy from solar radiation may be the best option for fish drying by using closed drying (greenhouse). This study aims to determine the effect of inlet velocity of air to the thermal performance of greenhouse in the no-load conditions by considering several environmental parameters such as temperature, humidity and solar radiation. The half an hourly data for ambient temperature, outlet temperature, relative humidity of air, wind velocity, radiation intensity were taken inside and outside the greenhouse dryer. These data are used for the determination of thermal performance of active greenhouse dryer. From experimental results, it can be concluded that drying conditions with inlet velocity of air 0,8 m/s is more favorable than inlet velocity of air 1,6 m/s as obtained thermal efficiency of active greenhouse is higher.